Doped ion modification method for manganese dioxide positive electrode of aqueous zinc ion battery

Through three-stage dynamic electrochemical deposition and ozone activated crystallization, the continuous concentration gradient doping structure is constructed in the manganese dioxide positive electrode material, which solves the problem of difficult to take into account both ion diffusion and structural stability in traditional processes, and improves the electrochemical performance of zinc ion batteries.

CN120545295APending Publication Date: 2025-08-26HUNAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510736405.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the ion diffusion kinetics and structural stability of manganese dioxide positive electrode materials. Traditional doping processes are prone to insufficient electronic conductance or instability of lattice structure. The electrolyte concentration regulation lacks dynamic gradient design, which affects the cyclic stability and rate performance of zinc ion batteries.

Method used

Three-stage dynamic electrochemical deposition is used to construct a dual-ion doped structure from the body phase to the surface, combined with ozone activation crystallization, the continuous gradient distribution of charge-compensated high-valent metal ions and lattice-stable metal ions is realized, and the concentration changes are controlled through a specific functional relationship to avoid elemental segregation caused by high-temperature annealing.

Benefits of technology

The structural stability and electrochemical performance of the positive electrode material of zinc ion battery are improved, the zinc ion diffusion path is optimized, the electrode/electrolyte contact area is increased, and the material's cycle stability and rate performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120545295A_ABST
    Figure CN120545295A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery manganese dioxide positive electrode doped ion modification method, belongs to the technical field of zinc ion battery preparation, and aims to solve the problem that ion diffusion kinetics and structural stability are difficult to consider in traditional uniform doping. The method comprises the steps that through three-stage dynamic electrochemical deposition, a continuous concentration gradient distribution double-ion doping structure from a bulk phase to a surface is constructed in a manganese dioxide lattice, double ions are charge compensation type high-valence metal ions and lattice stable type metal ions, and the electrolyte replacement rate and concentration linear change function parameters are controlled; and activating and crystallizing by ozone to synchronously realize high-valence ion oxidation and crystalline phase conversion from amorphous MnO2 to alpha-MnO2 so as to form a nanowire morphology. According to the method, electrochemical behavior consistency is guaranteed, a zinc ion diffusion path is optimized, lattice distortion is inhibited, electron conductivity and contact area are increased, structural stability and electrochemical performance of the material are comprehensively improved, and key indexes such as cycling stability and rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc ion battery preparation, and in particular to a method for modifying a manganese dioxide positive electrode of an aqueous zinc ion battery by doping with ions. Background Art

[0002] In the field of aqueous zinc-ion batteries, doping and modification of manganese dioxide cathode materials is a key technical direction for improving battery performance. Conventional uniform doping methods struggle to balance ion diffusion dynamics and structural stability. In a single uniform doping mode, focusing on introducing lattice-stabilizing ions to suppress lattice distortion often leads to insufficient electronic conductivity and reduced charge transfer efficiency. While simply increasing the amount of charge-compensating ions can improve electronic conductivity, it can easily lead to lattice structural instability, exacerbating capacity decay during cycling.

[0003] Furthermore, traditional high-temperature annealing processes often cause segregation of doping elements during phase transformation, disrupting the uniformity of the material composition and, in turn, affecting the consistency of electrochemical behavior. Furthermore, the existing doping process lacks a dynamic gradient design for electrolyte concentration control, making it prone to concentration step changes. This can lead to interfacial stress concentration, resulting in non-uniform diffusion paths and hindering the efficient migration of zinc ions.

[0004] In terms of material structure control, traditional methods have difficulty simultaneously achieving the targeted transformation of amorphous manganese dioxide into a specific crystalline phase and the oxidative activation of high-valent ions. Furthermore, the resulting material is mostly granular, with limited electrode / electrolyte contact area and a lack of optimized ion diffusion channels, which limits further improvements in the material's electrochemical performance. These issues make it difficult for existing manganese dioxide cathode materials to meet the application requirements of high-performance aqueous zinc-ion batteries in key indicators such as cycle stability and rate performance. Summary of the Invention

[0005] The main purpose of the present invention is to provide a method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions, which can effectively solve the problems mentioned in the background technology.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions comprises the following steps: S1. Gradient doping deposition: On a conductive substrate, a dual-ion doping structure with a continuous concentration gradient distribution from the bulk to the surface is constructed in the manganese dioxide lattice through three-stage dynamic electrochemical deposition; The dual ions include: charge-compensating high-valent metal ions and lattice-stabilizing metal ions, wherein the charge-compensating high-valent metal ions are selected from V 5+ 、Nb 5+ 、Ta 5+At least one of the lattice-stabilizing metal ions is selected from Al 3+ Mg 2+ 、Ti 4 + At least one of; S1.1 Bulk deposition: Immerse the substrate in an electrolyte containing: 0.05 to 0.15 mol / L lattice-stabilized ion source, 0.05 mol / L MnSO4, 0.1 mol / L Na2SO4, pH adjusted to 3-5, at 60-80°C with a flow rate of 0.05-0.2 mA / cm 2 Constant current deposition for 40-70 minutes to form a bulk region with a lattice-stabilized ion doping amount of 5-8at%; S1.2, Gradient transition deposition: During the deposition process, the charge-compensating ion source solution is continuously injected into the electrolyte at a rate of 0.5-1.5 mL / min, and the original electrolyte is simultaneously pumped out at an equal flow rate, so that the concentration of the lattice-stabilizing ions decreases linearly from the initial value to 0 and the concentration of the charge-compensating ions increases linearly from 0 to 0.05-0.10 M. The deposition is carried out for 10-30 minutes; S1.3. Surface deposition: In an electrolyte containing 0.05-0.10 mol / L charge-compensating ion source, 0.05 mol / L MnSO4, and 0.1 mol / L Na2SO4, maintain the same current density for 20-40 minutes to form a surface region with a charge-compensating ion doping amount of 3-6 at%; S2. Ozone-activated crystallization: Place the deposited electrode in a closed reactor, introduce an Ar / N2 mixed gas containing 10-30 vol% O3 (total flow rate 30-60 mL / min), increase the temperature to 120-180°C at 5°C / min and keep it at that temperature for 1-3 hours, to simultaneously achieve the high-valent oxidation of charge-compensating ions and the transformation of amorphous MnO2 to α-MnO2 crystal phase.

[0007] By dynamically controlling the electrolyte ion concentration in stages, a continuous gradient doping process from the bulk (high structural stability) to the surface (high charge transfer efficiency) is achieved, resolving the conflict between ion diffusion dynamics and structural stability in traditional uniform doping. Low-temperature ozone crystallization simultaneously completes high-valence ion oxidation and crystal phase transformation, avoiding element segregation caused by high-temperature annealing.

[0008] Preferably, the lattice-stabilized ion source is Al2(SO4)3, MgSO4 or TiOSO4; the charge-compensated ion source is VOSO4, NbCl5 or TaCl5; and the electrolyte replacement rate in step S1.2 is 5-10 mL / min.

[0009] Limit water-soluble ion source compounds such as Al2(SO4)3 to ensure the homogeneity of the deposition reaction; the electrolyte replacement rate of 5-10mL / min ensures a linear concentration gradient (R 2 ≥0.97), blocking the interfacial stress concentration caused by the concentration step.

[0010] Preferably, the linear change of concentration in step S1.2 needs to satisfy the following functional relationship: ,

[0011] in: : Lattice-stabilizing ion concentration at the moment (unit: mol / L) : Initial concentration of gradient deposition, 0.05-0.15 mol / L : Charge-compensating ion concentration at time t (unit: mol / L) : Lattice-stabilizing ion concentration deceleration rate, ranging from 0.005–0.015 mol / (L·min) : Charge compensation type ion concentration increasing rate, value is 0.003–0.010 mol / (L·min) : Sedimentation time (unit: minutes), range 0–30min.

[0012] function The concentration of the forced lattice-stabilizing ions decreases linearly with The controlled charge compensation ion increases to form a kinetic equilibrium, which stabilizes the concentration gradient slope in the transition zone at 0.08-0.12at% / nm (optimized Zn 2+ diffusion paths).

[0013] Preferably, the parameters of the function satisfy: =0.010±0.002mol / (L·min), =0.007±0.001mol / (L·min), and the linearity of the cross-sectional element distribution after gradient deposition is R 2 ≥0.97.

[0014] =0.010±0.002mol / (L·min) and =0.007±0.001mol / (L·min) was optimized by orthogonal experiments to ensure that the full concentration switching was completed within a 30min deposition cycle; R2 ≥0.97 requires the exclusion of nonlinear concentration fluctuations to ensure the consistency of bulk-surface electrochemical behavior.

[0015] Preferably, the charge-compensating ion is V 5+ , the lattice-stabilizing ion is Al 3+ ; Al in step S1.1 3+ The doping amount is 6.5±0.5at% in step S1.3. 5+ The doping amount is 4.5±0.5at%, and the concentration gradient slope in the transition zone is 0.10±0.02at% / nm.

[0016] V 5+ / Al 3+ In the combination, Al 3+ (0.535Å) Small radius suppresses Jahn-Teller distortion, V 5+ High charge enhances electronic conductivity; 6.5±0.5at% bulk doping reduces lattice expansion by less than 2%, and 4.5±0.5at% surface doping reduces charge transfer resistance by 40%.

[0017] Preferably, the material after ozone crystallization in step S2 must meet the following requirements: XRD characteristics: (310) crystal plane peak intensity ratio at 2θ=37.5° I (310) / I (110) ≥1.5; Oxidation state: XANES analysis shows a VK-edge absorption threshold of 5468±1eV; Morphology: SEM showed that the nanowire diameter was 50±10nm and the aspect ratio was >20.

[0018] I (310) / I (110) ≥1.5 locked 2×2 tunnel structure of α-MnO2 (Zn 2+ diffusion channel); 5468±1eV absorption edge confirms V 5+ Occupancy (providing additional free electrons); nanowire morphology (aspect ratio > 20) increases the electrode / electrolyte contact area.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention constructs a dual-ion doping structure with a continuous concentration gradient distribution from the bulk to the surface in the manganese dioxide lattice through three-stage dynamic electrochemical deposition. The dual ions include charge-compensating high-valent metal ions and lattice-stabilizing metal ions, and ozone-activated crystallization is used to simultaneously achieve high-valent oxidation of the charge-compensating ions and conversion of amorphous MnO2 to α-MnO2 crystalline phase. At the same time, the replacement rate of the ion source compound and the electrolyte is limited, and the concentration linear change is controlled through a specific functional relationship and the function parameters are optimized. This solves the contradiction between the ion diffusion dynamics and structural stability in traditional uniform doping, avoids element segregation caused by high-temperature annealing, ensures the consistency of electrochemical behavior from the bulk to the surface, optimizes the zinc ion diffusion path, suppresses lattice distortion with the help of lattice-stabilizing ions, improves electronic conductivity with charge-compensating ions, increases the electrode / electrolyte contact area through the α-MnO2 crystal phase structure and nanowire morphology, and comprehensively improves the structural stability and electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the modification process of the present invention. DETAILED DESCRIPTION

[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described below in conjunction with specific implementation methods.

[0022] like Figure 1 The process flow of the method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions is shown, and is described below in conjunction with a detailed embodiment.

[0023] 1. Gradient doping deposition stage Objective: To construct dual ion (charge-compensating high-valent metal ion V) from bulk to surface through three-stage dynamic electrochemical deposition. 5+ With lattice-stabilized metal ions Al 3+ ) Continuous concentration gradient distribution structure.

[0024] S1.1 Bulk Deposition Electrolyte preparation: Weigh 0.05mol / L MnSO4 (manganese sulfate), 0.1mol / L Na2SO4 (sodium sulfate), add Al2(SO4)3 (aluminum sulfate) to the lattice stable ion (Al 3+ ) concentration is 0.10 mol / L (in the range of 0.05-0.15 mol / L).

[0025] Adjust the pH to 4 (range 3-5) with dilute sulfuric acid and stir magnetically for 30 minutes until completely dissolved.

[0026] Deposition conditions: Nickel foam was selected as the conductive substrate (pretreatment: soaking in 1 mol / L HCl for 10 minutes to remove the oxide layer, and rinsing with deionized water until neutral).

[0027] The substrate was immersed in the electrolyte and placed in a constant temperature water bath at 60 °C at 0.1 mA / cm 2 Galvanostatic deposition was performed for 60 minutes (range 40-70 minutes).

[0028] Principle description: Low current density and low temperature environment promote Al 3+ Uniformly embedded in the MnO2 lattice to form a bulk region. 3+ (Ionic radius 0.535Å) By filling the MnO2 tunnel structure, Jahn-Teller distortion is suppressed and lattice stability is improved.

[0029] result: Bulk region Al 3+ The doping amount is 6.5at% (detected by EDS energy spectrum, in the range of 5-8at%), forming an initial stable skeleton.

[0030] S1.2 Gradient transition deposition Dynamic control of electrolyte: Injection solution: Prepare 0.2 mol / L VOSO4 (vanadium oxysulfate) solution as a charge compensation ion source (V 5+ precursor).

[0031] Replacement rate: Simultaneously inject VOSO4 solution and pump out the original electrolyte at a rate of 1.0 mL / min (in the range of 0.5-1.5 mL / min, preferably the lower limit of 5-10 mL / min).

[0032] Concentration function control: Lattice-stabilizing ions (Al 3+ ) concentration according to the formula Decreasing, where =0.010mol / (L·min).

[0033] Charge-compensating ions (V 5+ Precursor) concentration according to the formula Incremental, where =0.007mol / (L·min).

[0034] Example calculation: When deposition time =20min, =0.007×20=0.14mol / L (close to the target surface concentration of 0.05-0.10M, which will be further adjusted in the subsequent surface deposition stage).

[0035] Deposition conditions: Maintain current density 0.1 mA / cm 2 , deposited for 20 minutes (within the 10-30 minute range).

[0036] Principle description: The linear concentration gradient avoids the “concentration step” of the traditional process, prevents the structural defects caused by interface stress concentration, and optimizes the Zn 2+ Diffusion path (gradient slope controlled at 0.10±0.02at% / nm).

[0037] result: Al is formed in the transition zone 3+ The concentration dropped from 6.5 at% to 0, V 5+ The precursor concentration increases continuously from 0 to about 3.5 at%, and the element distribution linearity R 2 =0.98.

[0038] S1.3 Surface Deposition Electrolyte preparation: Replace with a solution containing 0.08 mol / L VOSO4, 0.05 mol / L MnSO4, and 0.1 mol / L Na2SO4, maintaining the pH at 4.

[0039] Deposition conditions: The same current density is 0.1mA / cm 2 The solution was allowed to settle for 30 minutes (range 20-40 minutes).

[0040] Principle description: High concentration V 5+ The precursor is enriched on the surface, and its high charge (+5) is used to improve the electronic conductivity and reduce the charge transfer resistance.

[0041] result: Surface area V 5+ The doping amount is 4.5at% (detected by XPS, in the range of 3-6at%), forming a highly conductive surface layer.

[0042] 2. Ozone activation crystallization stage Goal: Synchronous implementation of V 5+ High valence oxidation (from V 4+ →V 5+ ) and the transformation of amorphous MnO2 into α-MnO2 crystal phase to avoid element segregation during high temperature annealing.

[0043] Steps: The deposited electrode was placed in a closed reactor and an Ar / N2 mixed gas containing 20 vol% O3 was introduced.

[0044] Heat to 150°C (within the range of 120-180°C) at a heating rate of 5°C / min and keep warm for 2 hours.

[0045] Principle description: Ozone is a strong oxidant that can oxidize V 4+ Oxidized to V 5+ (The VK-edge absorption threshold detected by XANES is 5468eV, confirming that V 5+ exists), while inducing the directional growth of amorphous MnO2 into α-MnO2 crystal phase.

[0046] Low temperature environment inhibits Al 3+ With V 5+ Diffusion and agglomeration of elements can be achieved, avoiding the element segregation in traditional high-temperature processes.

[0047] Morphology control: After crystallization, SEM observation revealed the formation of a nanowire structure with a diameter of 50 nm (±10 nm) and an aspect ratio of 25 (>20), which significantly increased the electrode / electrolyte contact area (the specific surface area was increased to three times that of traditional granular materials).

[0048] 3. Performance Test and Results Cyclic stability: After 500 cycles at a current density of 1 A / g, the capacity retention rate reaches 85% (only 60% for the traditional uniform doping process), which is attributed to the Al 3+ Bulk stable lattice and V 5+ Synergistic effect of fast surface charge transfer.

[0049] Rate performance: The current density is increased from 0.5A / g to 5A / g, and the capacity retention rate is 78% (only 55% for the traditional process). The nanowire morphology and gradient structure optimize the Zn 2+ Diffusion path.

[0050] Structural characterization: XRD confirmed the purity of α-MnO2 crystal phase (peak intensity ratio 1.6 at 22θ=37.5°), and XPS confirmed V 5+ Oxidation state (binding energy 517.5 eV), EDS line scan shows Al 3+ / V 5+ The concentration gradient linearity was good (R 2 =0.98).

[0051] Summary of Examples This embodiment successfully constructed a gradient doping structure of "high bulk stability and high surface conductivity" through three-stage dynamic concentration control and ozone low-temperature crystallization, resolving the contradiction between ion diffusion and structural stability in traditional processes. At the same time, the electrochemical performance was synergistically improved by the nanowire morphology and α-MnO2 crystal phase, providing a new solution for high-performance aqueous zinc-ion battery positive electrode materials.

[0052] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for modifying the manganese dioxide cathode of an aqueous zinc ion battery by doping ions, characterized in that: The following steps are involved: S1. Gradient doping deposition: On a conductive substrate, a dual-ion doping structure with a continuous concentration gradient distribution from the bulk to the surface is constructed in the manganese dioxide lattice through three-stage dynamic electrochemical deposition; The dual ions include: charge-compensating high-valent metal ions and lattice-stabilizing metal ions, wherein the charge-compensating high-valent metal ions are selected from V 5+ 、Nb 5+ 、Ta 5+ At least one of the lattice-stabilizing metal ions is selected from Al 3+ Mg 2+ 、Ti 4+ At least one of; S1.1, Bulk Deposition: Immerse the substrate in an electrolyte containing: 0.05 to 0.15 mol / L lattice-stabilized ion source, 0.05 mol / L MnSO4, 0.1 mol / L Na2SO4, pH adjusted to 3-5, at 60-80 ° C with a flow rate of 0.05-0.2 mA / cm 2 Constant current deposition for 40-70 minutes to form a bulk region with a lattice-stabilized ion doping amount of 5-8at%; S1.2, Gradient transition deposition: During the deposition process, the charge-compensating ion source solution is continuously injected into the electrolyte at a rate of 0.5-1.5 mL / min, and the original electrolyte is simultaneously pumped out at an equal flow rate, so that the concentration of the lattice-stabilizing ions decreases linearly from the initial value to 0 and the concentration of the charge-compensating ions increases linearly from 0 to 0.05-0.10 M. The deposition is carried out for 10-30 minutes; S1.3, surface deposition: in an electrolyte containing 0.05-0.10 mol / L charge-compensating ion source, 0.05 mol / L MnSO4 and 0.1 mol / L Na2SO4, maintain the same current density for 20-40 minutes to form a surface region with a charge-compensating ion doping amount of 3-6 at%; S2. Ozone-activated crystallization: Place the deposited electrode in a closed reactor, introduce an Ar / N2 mixed gas containing 10-30 vol% O3 at a total flow rate of 30-60 mL / min, increase the temperature to 120-180°C at a rate of 5°C / min, and keep the temperature for 1-3 hours to simultaneously achieve high-valent oxidation of charge-compensating ions and conversion of amorphous MnO2 to α-MnO2 crystal phase.

2. A method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions according to claim 1, characterized in that: The lattice-stabilized ion source is Al2(SO4)3, MgSO4 or TiOSO4; the charge-compensated ion source is VOSO4, NbCl5 or TaCl5; and the electrolyte replacement rate in step S1.2 is 5-10 mL / min.

3. A method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions according to claim 1, characterized in that: The linear change of concentration in step S1.2 must satisfy the following functional relationship: C comp (t)=k2·t in: C stable (t): lattice-stabilizing ion concentration at time t, The initial concentration of gradient deposition is 0.05-0.15 mol / L. C comp (t): charge compensation ion concentration at time t, k1: the rate of decrease of lattice-stabilizing ion concentration, ranging from 0.005 to 0.015 mol / (L·min), k2: the rate of increase in charge compensation ion concentration, ranging from 0.003 to 0.010 mol / (L·min), t: deposition time, range 0–30 min; Specifically: k1 = 0.010 ± 0.002 mol / (L·min), k2 = 0.007 ± 0.001 mol / (L·min), and the linearity of the cross-sectional element distribution after gradient deposition R 2 ≥0.

97.

4. A method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions according to claim 1, characterized in that: The charge compensating ion is V 5+ , the lattice-stabilizing ion is Al 3+ ; Al in step S1.1 3+ The doping amount is 6.5±0.5at% in step S1.

3. 5+ The doping amount is 4.5±0.5at%, and the slope of the transition zone concentration gradient is 0.10±0.02at% / nm.

5. A method for modifying the manganese dioxide positive electrode of an aqueous zinc ion battery by doping ions according to claim 1, characterized in that: The material after ozone crystallization in step S2 must meet the following requirements: XRD characteristics: (310) crystal plane peak intensity ratio at 2θ=37.5° I (310) / I (110) ≥1.5; Oxidation state: XANES analysis shows a VK-edge absorption threshold of 5468±1eV; Morphology: SEM showed that the nanowire diameter was 50±10nm and the aspect ratio was >20.